A Geo-historical Analysis of Expanding Soybean Frontiers in the Brazilian Cerrado - Rocha, Cassiano Brito; Majo, Claudio de; Dutra e Silva, Sandro (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
Until the 1970s, the Brazilian Cerrado was considered an unsuitable agricultural territory. Logistic and infrastructural issues, combined with soil acidity, made the Cerrado a marginal biome for crop production. However, since the Brazilian Agricultural Research Corporation (Embrapa) was created in 1973, the Cerrado has become a national and international hotspot for the food industry. Such a transformation turned this savannah biome into a landmark for the tropical expansion of commodity frontiers, especially in soy production. This research seeks to analyze data on the historical development of soy production volumes and productivity in the Cerrado, considering the complex interrelations between commodity frontier dynamics and its interface within different Brazilian biomes. Comparing data from the Cerrado and other biomes, our results indicate a rapid expansion of the soybean frontier in most Brazilian biogeographic regions. Moreover, it demonstrates how the growth of soy farming in the Brazilian Cerrado is also affecting other biomes such as the Amazon, influencing local and national policies of agrarian expansion and environmental conservation.